The influence of task demands and implicit racial bias on face-sensitive visual ERPs to own- and other-race faces. - Anzures, Gizelle; Mildort, Melissa (Visual Cognition, 2024)
The present study examined the influence of task demands and participants' implicit racial biases on P100, N170, P200, and N250 responses to own- and other-race faces. White adults completed an Implicit Association Test (IAT) with White and Asian faces. They also completed a face race categorization task and a face identity processing task with White and Asian faces while continuous EEG was recorded. Implicit racial bias as well as its interaction with task demands modulated early face-sensitive responses to own- and other-race faces. Adults with relatively larger implicit biases favoring their own race showed different ERP responses to own- and other-race faces later in their face processing and regardless of task demands. However, among adults with relatively smaller implicit biases favoring their own race, differences in ERP responses to own- and other-race faces occurred earlier and was task dependent.